Structural Model of Digital Transformation Readiness of Indonesian Rural and Urban Science Teachers - Rusydiyah, Evi Fatimatur; Asrohah, Hanun; Basyir, Kunawi; Rahman, Moh. Rifqi; Usagawa, Tsuyoshi (Universitas Negeri Semarang, 2024)
Technological and digital developments have implications for integrating technology into educational practice. As a result, teachers have to deal with digital transformation. This research aims to compare the digital transformation readiness of science teachers in urban and rural areas. This research compares to the previously determined structural model of digital transformation readiness. This research used a survey method to test several research hypotheses. The respondents of this research were 206 science teachers in Indonesia, selected using stratified random sampling to ensure a balanced representation of various sub-groups such as gender, geographic location, island, age, type and status of institution, and teaching experience. This research data was analyzed using AMOS 26 to analyze CBSEM. The research results show three main points in digital transformation: the self-efficacy of rural teachers is affected by digital literacy, the information empowerment of rural teachers is affected by information literacy and digital literacy, and the information use of rural teachers is affected by information culture. Urban teachers at these three points are more dependent and require recommendations for development and optimization. The conclusion of this research leads to a recommendation that, in general, teachers in rural areas still need improvements, while teachers in urban areas are already moving towards developing and sustaining their skills.